Talento humano y calidad del servicio hotelero en la ciudad de Puyo, provincia de Pastaza - Tomalá Andrade, Karen Fernanda (2025)
The study aimed to analyze the relationship between human talent and the quality of service provided in the hotel sector of the city of Puyo, located in the province of Pastaza. The research methodology employed a non-experimental, cross-sectional, correlational, and explanatory design, utilizing techniques such as structured interviews and surveys. Data were collected through surveys conducted in 47 hotel establishments, and their reliability was assessed using Cronbach's Alpha coefficient. The findings revealed that in three-star hotels, personalized, warm, and friendly service was offered, with a high degree of empathy, indicating that the staff were trained and possessed the appropriate knowledge for the functions they performed. However, in two- and onestar hotels, the service provided by the staff appeared more superficial, mainly due to a lack of understanding of customer service strategies and quality standards. It was concluded that implementing training programs for employees is essential to strengthen human talent and foster continuous improvement within each hotel establishment. In this regard, the knowledge, competencies, and skills of well-trained personnel significantly impact the quality, safety, and reliability of a hotel, thereby building trust, confidence, and customer loyalty. Therefore, a seminar guide is proposed to train and develop human talent in Puyo's hotel industry, aiming to strengthen it.